Hubungan Kualitas Tidur Dengan Tekanan Darah - Widya Kusumaningrum; Rosalina Rosalina; Umi Setyoningrum (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2020)
Good quality sleep gets fresh and healthy when awakened from sleep. Poor sleep quality is a risk factor for physical and psychological problems. The problem will arise activating the sympathetic nervous system which eventually causes an increase in blood pressure. So it is important to research because there are still many respondents who experience poor sleep quality with increasing blood pressure. To determine the correlation between sleep quality with blood pressure. Research design descriptive corellational with cross sectional approach. Population in this study is students of PSIK at Ngudi Waluyo University. The sample technique used purposive sampling. The number of samplesÂ is 78 respondents. Analysis of research data used the Spearman Rank Correlation test. The results showed that the students who experienced poor sleep quality were 70 respondents (89.7%). The highest blood pressure of the students was systolic blood pressure of 110 mmHg and diastolic blood pressure of 80 mmHg. On the relationship between sleep quality and systolic blood pressure with a coefficient (r) of 0.400, the strength of the relationship is interpreted at a low level. On the relationship between sleep quality and diastolic blood pressure with a coefficient (r) of 0.619, the strength of the relationship is interpreted at a high level. There was a significant correlation between sleep quality and blood pressure with p-value of 0,000 <0.05. It is expected that the respondents and the society should better regulate blood pressure in order to get good quality sleep.Key words: sleep qualityblood pressure